2021
DOI: 10.1101/2021.05.31.21255594
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Signatures of mast cell activation are associated with severe COVID-19

Abstract: Lung inflammation is a hallmark of Coronavirus disease 2019 (COVID-19) in severely ill patients and the pathophysiology of disease is thought to be immune-mediated. Mast cells (MCs) are polyfunctional immune cells present in the airways, where they respond to certain viruses and allergens, often promoting inflammation. We observed widespread degranulation of MCs during acute and unresolved airway inflammation in SARS-CoV-2-infected mice and non-human primates. In humans, transcriptional changes in patients req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 51 publications
0
25
0
Order By: Relevance
“…Moreover, platelets express high levels of ACE2 and, as a consequence, purified Spike protein may directly activate platelets, potentiating the prothrombotic cascade (9). Finally, since MCAS may be intimately involved in the pathogenesis of both severe form of acute COVID-19 infection and of COVID-19 "long-haul" syndrome through ACE2/Spike protein interactions (50,51), it may be speculated that the interplay of altered mast cells with neosynthesized SARS-CoV-2 spike protein could further contribute to VITT development.…”
Section: Timing Of the Symptoms Onsetmentioning
confidence: 99%
“…Moreover, platelets express high levels of ACE2 and, as a consequence, purified Spike protein may directly activate platelets, potentiating the prothrombotic cascade (9). Finally, since MCAS may be intimately involved in the pathogenesis of both severe form of acute COVID-19 infection and of COVID-19 "long-haul" syndrome through ACE2/Spike protein interactions (50,51), it may be speculated that the interplay of altered mast cells with neosynthesized SARS-CoV-2 spike protein could further contribute to VITT development.…”
Section: Timing Of the Symptoms Onsetmentioning
confidence: 99%
“…Mast cells are long-lived innate immune cells that not only provide the first line of host defense against viral and bacterial infections but also participate in the pathogenesis of allergic inflammation and neurological disorders ( Georgin-Lavialle et al, 2016 , Hendrikus et al, 2017 ). Emerging evidence has pointed to an involvement of mast cells in inflammatory syndrome associated with COVID-19 ( Tan et al, 2021 , Conti et al, 2020 ). Mast-cell-enriched mediators, such as carboxypetidase A3, chymase, tryptase, and serotonin, were elevated in sera of SARS-CoV2 infected patients and positively correlated with hyperinflammatory markers ( Soria-Castro et al, 2021 , Gebremeskel et al, 2021 ).…”
Section: Cellular Mediators Of Covid-19 Associated Hyperinflammationmentioning
confidence: 99%
“…Inflammatory mediators from mast cell activation are associated with severe COVID-19 [58]). By measuring mast cell-specific protease chymase, [58] Tan et al (2021) observed widespread degranulation of mast cells during airway inflammation in SARS-CoV-2-infected mice.…”
Section: Involvement Of Mast Cells In the Pathogenesis Of Covid-19mentioning
confidence: 99%
“…Inflammatory mediators from mast cell activation are associated with severe COVID-19 [58]). By measuring mast cell-specific protease chymase, [58] Tan et al (2021) observed widespread degranulation of mast cells during airway inflammation in SARS-CoV-2-infected mice. They also confirmed widespread mast cell activation in COVID-19-infected primates by detecting heparin-containing granules in the lung tissue through fluorescence staining [58].…”
Section: Involvement Of Mast Cells In the Pathogenesis Of Covid-19mentioning
confidence: 99%
See 1 more Smart Citation